Socio – personal and Economic profile of Dairy Farmers in Palakkad District of Kerala - Anand Shankar; S. Pramod; V. Shankar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was conducted in Palakkad district of Kerala as a research activity of ASRTC Trust. A Schedule was developed to record socioeconomic profile of the respondents. Data was collected from 240 dairy farmers using questionnaires by personal interview method and was analysed with statistical tools like frequency and percentage. The distribution of farmers according to age observed in the present study was 51.7 per cent in middle age, 46.8 per cent in old age and 1.70 per cent in young age groups. Farmers with education of class X and less accounted for 75.88 per cent of respondents while 17.65 per cent were graduates and 4.12 per cent had post-graduation or higher education. Illiterate farmers accounted to 2.35 per cent of respondents. Majority of farmers were from OBC communities (46 %) followed by general (39 %) while SC/ST category accounted for 15 per cent of the respondents. Family size was small (less than 5) in 70.4 per cent of respondents and 27.9 per cent of farmers had medium sized families with 6-10 members. About 1.7 per cent of farmers had large families (more than 10 members). Majority of the respondents maintained small herds (65.8%) while 21.3 per cent had medium sized herds. Large herds were maintained by 12.9 per cent of respondents. Majority of the farmers (40.4%) belonged to medium income group, 33.8 per cent had low income and 25.8 per cent had high income. Most farmers had a landholding between 11 cents and up to one acre (45.08 %). Almost equal proportions of farmers had less than 10 cents (27.98 %) and more than 2 acres (26.94 %). Biogas plant was installed by 14.2 per cent of the respondents.